Pelatihan Financial Planning UMKM sebagai Kelayakan Usaha Bagi Ibu Rumah Tangga di Kelurahan Dukuh Setro, Kecamatan Tambak Sari - Dina Anggraeni Susesti; Endah Tri Wahyuningtyas (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
In the current era of the covid pandemic, many people losing their jobs, especially workers. Therefore, many housewives run small and micro businesses to fulfilling their needs. Unfortunately, many mothers did not do the recording properly and correctly in the implementation. The main problems that exist are the lack of financial planning and the lack of distinction between personal financial records and business finances. The purpose of this community service activity can provide a good solution for the sustainability of the business of housewives in Dukuh Setro, Tambak Sari District, Surabaya. We wish the business can grow perfectly.